Family Involvement Interventions in Child Protection: Learning from Contextual Integrated Strategies - Crampton, David Stuart (2004)
The use of family group conferencing and related family involvement interventions in child protection is rapidly increasing in the United States and many other countries. There is some concern that the child welfare field will travel down the same road as it did with intensive family preservation services; that is, tremendous enthusiasm later derailed by rigidly designed evaluations that showed unimpressive effects. The work of John Braithwaite suggests an alternative path for finding justifiable excitement about these interventions. Drawing upon Braithwaite's writings and ongoing evaluation research, this article suggests a few steps we can take towards an integrative strategy for developing effective family involvement interventions